Future trends in plant-based meat: Consumer perception, market growth and health benefits - Janifer Raj Xavier; Sahana Hevlin Shashikumar; Dimple Vats; Om Prakash Chauhan (Future Foods)
In time, meat analogues will become more widely availablebecause they are perceived by consumers as ''better for you'' and ''better for the planet'', plant-based goods are becoming increasingly well known. Soy proteins, wheat gluten, cotton seed proteins, and other plant proteins have been utilized to successfully create meat alternatives. Vegetable proteins with texture can be consumed as meat alternatives or as a more affordable, useful and higher-protein substitute for meat products. Meat replacements are popular owing to their low cost, meat-like texture and health benefits. During the COVID-19 pandemic, dietary modifications and Plant Based Meat (PBM) replacements were the main subjects of this investigation, as were the factors influencing consumer perception in various nations and the policies that can encourage the move towards PBM. In the upcoming years, it is anticipated that the PBM market will expand as awareness, familiarity and knowledge increase. If businesses wish to appeal to the target market, to help clients make the transition to a diet heavy in PBM replacements, they must concentrate on the areas of anticipated advantages.